Implementation of the Integrity Zone Development Policy at the Central Statistics Agency of East Nusa Tenggara Province - Dillak, Victor Edison; Kase, Petrus; Nursalam, Nursalam (Journal of Tourism Economics and Policy, 2026)
One government agency implementing the Integrity Zone (ZI) through the Corruption-Free Area (WBK) and Clean and Serving Bureaucracy Area (WBBM) approach is the Central Statistics Agency (BPS) of East Nusa Tenggara (NTT) Province. However, as of 2024, BPS NTT has not yet achieved WBK or WBBM status from the Ministry of Administrative and Bureaucratic Reform. This study aims to analyze the implementation of the Integrity Zone development policy at BPS NTT. A descriptive qualitative approach was employed, with data collected from primary and secondary sources involving 15 informants. Data analysis followed Creswell’s qualitative analysis techniques. The analysis is based on the policy implementation model proposed by Van Meter and Van Horn, which consists of six variables. The findings indicate that policy standards and objectives are clear and measurable; policy resources are adequate; inter-organizational communication and coordination are well established; implementers demonstrate discipline and a strong sense of responsibility; social, economic, and political conditions are supportive; and implementers’ dispositions positively influence policy implementation. Supporting factors include strong leadership commitment, a mature monitoring and evaluation system, a culture of innovation, and high public demand. Meanwhile, inhibiting factors include limited employee understanding of change agent roles, uneven internet network coverage, respondent burden, and budgetary dynamics. Overall, the implementation of the Integrity Zone policy at BPS NTT shows positive progress but still faces structural and technical challenges.